Characterization of ion conducting solid biopolymer electrolytes based on starch-chitosan blend and application in electrochemical devices / Muhammad Fadhlullah Abd. Shukur - Muhammad Fadhlullah, Abd. Shukur (2015)
In this work, the aim is to develop a solid polymer electrolyte (SPE) system based on biopolymer. From X-ray diffraction (XRD) technique, the blend of 80 wt.% starch and 20 wt.% chitosan is found to be the most amorphous blend. This starch-chitosan blend ratio is used as the polymer host in preparation of two SPE systems (salted and plasticized) via solution cast technique. Interaction between the materials is confirmed by Fourier transform infrared (FTIR) spectroscopy analysis. In the salted system, the incorporation of 25 wt.% ammonium chloride (NH4Cl) has optimized the room temperature conductivity to (6.47 ± 1.30) × 10-7 S cm-1. In the plasticized system, the conductivity is enhanced to (5.11 ± 1.60) × 10-4 S cm-1 on addition of 35 wt.% glycerol. The conductivity is found to be influenced by the number density (nd) and mobility (μ) of ions. Conductivity trend is verified by XRD, scanning electron microscopy (SEM) and differential scanning calorimetry (DSC) results. The temperature dependence of conductivity for all electrolytes is Arrhenian. From transference number of ion (tion) measurement, ion is found as the dominant conducting species. Transference number of cation (t+) for the highest conducting electrolyte (P7) is found to be 0.56. Linear sweep voltammetry (LSV) result confirms the suitability of P7 electrolyte to be used in the fabrication of an electrochemical double layer capacitor (EDLC) and proton batteries. The EDLC has been characterized using galvanostatic charge-discharge and cyclic voltammetry (CV) measurements. The primary proton batteries have been discharged at different constant currents. The secondary proton battery has been charged and discharged for 40 cycles.